"The Author's Empty House" Revisited. - Hepburn, James (Sewanee Review)
The author relates the authorship of his book to the first half of its title. He mentions the disagreement between authors and publishers, and the role of literary agents in the publication of the book which left authors with empty purse. The author narrates his personal experience with the authorship of his broadside ballad book.